Homodyne-based quantum random number generator at 2.9 Gbps secure against quantum side-information - Tobias Gehring (Nature Portfolio, 2021)
Security analyses for trusted quantum random number generators usually consider only classical side-information. Here, the authors fill this gap by fully characterising the experimental apparatus of a homodyne-based QRNG, assuming that the vacuum fluctuations and noise are stationary and Gaussian.